Amantadine in the Treatment of Pathological Gambling: A Case Report - Pettorruso, Mauro; Martinotti, Giovanni; Di Nicola, Marco; Onofrij, Marco; Conte, Gianluigi; Di Giannantonio, Massimo; JANIRI, LUIGI (Frontiers in Psychiatry, 2012)
Despite almost a decade of intense research, effective treatment strategies for Pathological Gambling (PG) remain very challenging. This paper details a case report suggesting that the treatment of PG may benefit from the use of the non-specific glutamate blocker amantadine. The drug was well-tolerated and effective, leading to a 43% - 64% reduction in severity of gambling symptoms (as measured with G-SAS). Our result is discussed in the context of the glutamatergic hypothesis of addiction and in light of previous observations on the potential impact of glutamatergic agents in the treatment of PG. The role of the dopaminergic system, and its interaction with the glutamatergic system, is also explored. Further studies are required to define the true benefits of amantadine for the treatment of PG.